Community benefit agreements and natural resource development: Achieving better outcomes. (October 2021) - Gunton, Thomas; Werker, Eric; Markey, Sean
Abstract: Community benefit agreements have emerged as a popular tool for mitigating conflicts over natural resource development and generating benefits for local communities. While CBAs hold considerable promise as a means of improving resource development, there remains a wide variation in CBA outcomes and considerable uncertainty over their effectiveness. This collection of research papers seeks to reduce this uncertainty by summarizing the current state of knowledge on CBAs and advancing our understanding of the role of CBAs. The findings suggest that while CBAs have potential for improving outcomes from resource development, many CBAs fall short of expectations and improvements are required. The findings identify reforms and best practices for improving CBAs to achieve more sustainable development and methodological guidance for future research on CBAs and resource-led development. Highlights: Community benefit agreements (CBAs) are a popular tool for resolving conflicts in resource development. There is wide variation in CBA outcomes and uncertainty over their effectiveness. CBAs have potential for improving outcomes but many fall short of expectations. Reforms are required to improve CBAS and to achieve more sustainable development.